Human response against NP-4, a mouse antibody to carcinoembryonic antigen: human anti-idiotype antibodies mimic an epitope on the tumor antigen. - Losman, M J (1991)
Anti-idiotype antibodies (Ab2) were purified from a cancer patient treated with NP-4, a murine monoclonal antibody to carcinoembryonic antigen (CEA). These Ab2 were specific for NP-4 and inhibited the binding between NP-4 and CEA. BALB/c mice immunized with these human Ab2 produced anti-Ab2 antibodies that were also reactive with the CEA epitope recognized by NP-4. These results indicate that human Ab2 to NP-4 can antigenically mimic the CEA epitope recognized by NP-4.